BERPIKIR KREATIF MATEMATIS DAN KEMANDIRIAN BELAJAR DALAM PEMBELAJARAN BERBASIS MASALAH - Nanang, Asep (Universitas Pendidikan Indonesia, 2016)
This study focuses on problem-based learning that can be used as an alternative effort to improve self-regulated learning and mathematical creative thinking abilities of elementary school students. Considering that most of the primary schools only apply expository learning, cognitive abilities were measured only limited computational capability without creativity, so did the affective aspect which seems to be less developed as well as aspects of self-regulated learning Therefore, the presence of problem-based learning is expected to address both of these issues, in which the mathematical creative thinking abilities may increase, coupled with the growing students’ self-regulated learning Through the experimental method in a population of students in middle achiever elementary school category, in one of the districts in West Java, the result shows that problem-based learning can improve the mathematical creative thinking abilities and self-regulated learning of elementary school students.Keywords: problem-based learning, mathematical creative thinking abilities, self-regulated learning.